Analysis of the Stop Work Authority (SWA) Program and Development of a Microlearning Training Module for Construction Workers - Farhan Alparizi; Joko Wintoko (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Construction projects with high risk levels require strong occupational safety and health systems, yet the implementation of the Stop Work Authority program often faces challenges such as uneven risk understanding, ineffective communication, limited training, and weak safety culture. Objective: This study aims to evaluate the influence of risk understanding, Stop Work Authority understanding, communication, and training on safety compliance, and to develop microlearning-based electronic learning media to enhance program effectiveness. Method: A quantitative descriptive cross-sectional survey was conducted involving construction workers, supervisors, and safety officers in a building project at Universitas Gadjah Mada, with 84 respondents selected from a population of 106. Data were collected using a validated and reliable Likert-scale questionnaire, supported by observations and interviews, and analyzed using descriptive statistics and multiple linear regression with classical assumption testing. Result and Discussion: The findings show that all variables are in good to very good categories, and all independent variables have a significant positive effect on safety compliance. Strengthening these aspects contributes to improved worker behavior and program implementation. Conclusions: Enhancing risk understanding, communication, and structured training supported by microlearning-based electronic learning is essential to improve safety compliance and strengthen safety culture in construction projects.